KEKUATAN KARYA SASTRA MUHAMMAD IQBAL DAN PENGARUHNYA TERHADAP MASYARAKAT ISLAM INDIA - Ahmad Ghozi (El-QUDWAH, 2013)
KEKUATAN KARYA SASTRA MUHAMMAD IQBAL DAN PENGARUHNYA TERHADAP MASYARAKAT ISLAM INDIA Oleh: Ahmad Ghozi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang Jl. Gajayana No. 50, Malang. Telp. 081555788548 e-mail: cakrawala.bangsa@gmail.com Abstract Literary work is a mimesis, as a translation of fiction. Etymologically, fiction derived from the root of a finger (latin) means the pretense. On the novel, the author as a writer as well as figures that play basically just considered to be feigned.But precisely because of that, mock impersonate via a character invented and portrayed in literary works become interesting.Furthermore the literary work into a work of value after going through the reading by the readers, researchers and connoisseurs. Literary talk about life and the life, about various problems of human life, about life around humans, about life in General, all of which is in the way and reveal a distinctive language.It means that good way the disclosure of or language which is used to express various problems of life, or commonly called the idea, is a typical literature, distinctive in the other definitions than others.Namely, it contained element and the purpose of beauty, more nuanced performance beauty rather than practicability.Muhammad Iqbalmade literature as a tool to motivate and encourage Indian people to dare change life, Muhammad Iqbalalso separates himself to humanity,Then his works just keep going to create peace managing civilization and transport people on goal in life. Key words: Literature, motivation and social movement